Performance evaluation of GPS/Galileo fractional cycle bias products and PPP ambiguity resolution. Issue 3 (2nd September 2022) - Lin, Jiale; Qiao, Shubo; Xiao, Guorui; Du, Zhenqiang
ABSTRACT: To compare and evaluate the performance of different multi-GNSS fractional cycle biases (FCBs) products and precise point positioning (PPP) ambiguity resolution. We compare the stability and positioning performance of the School of Geodesy and Geomatics (SGG) and CNES GPSFCBs products. The results show that similar stability and high consistency are observed between the two products, the difference of PPP ambiguity resolution bias between them is in the level of millimetre. And it is found that the epoch-interval of narrow-lane FCBs can be enlarged from 15 min to 30-180 min, to ease the transmission pressure on the transmission link.